The Effect of One Laptop per Child on Teachers' Pedagogical Practices and Students' Use of Time at Home - Gustavo Yamada; Pablo Lavado; Guadalupe Montenegro (Institute of Labor Economics (IZA), 2016)
This document investigates the effect that the delivery of XO laptops in Peru has had on teachers' pedagogical practices and students' use of time in the home based on information from a randomized control trial. The results show that the delivery of XO laptops reduces the probability that teachers will use a student-centered method with cooperative characteristics between 6 and 13 pp while this type of pedagogical practice has a positive impact on student performance in the area of language (between 1.5 and 2sd). We found two contrary effects in the home. XO laptops reduce the probability that a student will do homework at home by 4 pp despite the fact that doing so increases language performance 4 standard deviations. Additionally, XO laptops increase the probability of watching television by 8 pp although said activity reduces performance 2 sd. XO laptops also reduce the probability that students will perform household chores between 9 and 40 pp while said activity increases language performance between 0.2 and 1.6 standard deviations for language. We did not find effects on language and the majority of results refer to students in fourth grade of primary. The variety and overlapping of effects may explain the null effect of the program for the sample of 2nd to 6th grade of primary and the negative effect for fourth of primary.
Keywords: C13; C93; I21; I28; 330; education; technology; teacher; teaching methods; pedagogical practices; academic performance; laptop; OLPC; time; activities; household